Analisis Perencanaan Kampanye Pemasaran Sosial "Kobarkan Kebaikan" Pertamina - Asep Sutresna (ULTIMA Comm, 2018)
ABSTRACTThis research aims to analyze the planning strategy of Pertamina in managing social marketing campaign "Kobarkan Kebaikan” (Flame the Goodness). This campaign was initiated based on an assessment of the society which was disintegrated by the Jakarta gubernatorial election in 2017 and the presidential and legislative campaign in 2019 started in 2018. The campaign materials were made by the society and broadcasted through the television and youtube. Based on media ecology theory, media directly form and develop culture, which is also the case with the media selection in the "Kobarkan Kebaikan” campaign. This research gathers qualitative data based on the planning model of Social Marketing Planning Primer (SMPP) by Kotler and Lee (2016). This research shows this campaign has a positive impact on the engagement and results in message amplification. From the perspective of planning, this research fell short of the criteria required by the SMPP model Keywords: Pertamina, Kobarkan Kebaikan, Social Marketing, social campaign